Akhlak dan Pembentukan Karakter Seseorang - Noor Khimzatun (Jurnal Syntax Transformation, 2021)
A Muslim is required to have adab or morals in everyday life. The author believes and realizes that the teachings of Islam are so extraordinary, that the whole joints of life are arranged in such a way for the sake of harmony, continuity and order of human life. The various rules become bridges, things, norms, which must be followed by every adherent, so that life in this world can run well. Adab or ethics include various things, ranging from waking up to going to sleep, there is association in society, being a citizen, being a child, husband, or wife, including adab on the way, everything is arranged properly and detailed. This article tries to photograph a little of the various rules of life, so that it can be understood for the better. All objects of the discussion in order to provide guidance or reference for the community to create harmony, order, and mutual benefit in the family, school, community, in places of worship, on the streets, and the nation. This screenwriting uses library research methods in an effort to find out in more detail about the important role of morals in the formation of a person's character in general. The results of research obtained by humans are social creatures that have a relationship between each other interdependent and needy. A person will feel comfortable when living with similar creatures and will feel lonely when living alone. Therefore, one must have a good temperament in order to realize good survival in the midst of society